Characteristics of Skin Deposition of Itraconazole Solubilized in Cream Formulation - Kim, Hyeongmin (Pharmaceutics, 2019)
Itraconazole (ITZ) is an anti-fungal agent generally used to treat cutaneous mycoses. For efficient delivery of ITZ to the skin tissues, an oil-in-water (O/W) cream formulation was developed. The O/W cream base was designed based on the solubility measurement of ITZ in various excipients. A physical mixture of the O/W cream base and ITZ was also prepared as a control formulation to evaluate the effects of the solubilized state of ITZ in cream base on the in vitro skin deposition behavior of ITZ. Polarized light microscopy and differential scanning calorimetry demonstrated that ITZ was fully solubilized in the O/W cream formulation. The O/W cream formulation exhibited considerably enhanced deposition of ITZ in the stratum corneum, epidermis, and dermis compared with that of the physical mixture, largely owing to its high solubilization capacity for ITZ. Therefore, the O/W cream formulation of ITZ developed in this study is promising for the treatment of cutaneous mycoses caused by fungi such as dermatophytes and yeasts.